Mindfulness training in UK secondary schools: a multiple case study approach to identification of cornerstones of implementation - Wilde, S; Sonley, A; Crane, C; Ford, T; Raja, A; Robson, J; Taylor, L; Kuyken, W (Springer, 2018)
This paper examined the facilitators and barriers to implementation of mindfulness training (MT) across seven secondary/high schools using a qualitative case study design. Schools varied in level of implementation. Within schools, head teachers, members of school senior leadership teams, and staff members involved in the implementation of MT were interviewed individually. In addition, focus groups were conducted with other members of school staff to capture a broad range of views and perspectives. Across the case studies, several key themes emerged, which suggested four cornerstones to successful implementation of MT in schools. These were: people, specifically the need for committed individuals to champion the approach within their schools, with the support of members of the senior leadership teams; resources, both time and financial resources required for training and delivery of MT; journey, reflecting the fact that implementation takes time, and may be a non-linear process with stops and starts; and finally perceptions, highlighting the importance of members of the school community sharing an understanding what MT is and why it is being introduced in each school context. Similarities and differences between the current findings and those of research on implementation of other forms of school mental health promotion programs, and implementation of MT in healthcare settings, are discussed.